Review of Amy C. Beal. 2006. New Music, New Allies: American Experimental Music in West German from the Zero Hour of Reunification. Berkeley and Los Angeles: University of California Press. - Silverberg, Laura (Current Musicology, 2008)
To judge from the recent surge in publications on music of the Cold War, musicologists in increasing numbers are casting off the prejudices, anxieties and animosities that for decades blinkered scholarship on postwar music. Cold War divisions between the communist East and democratic West had once fostered the presumption that music intersected with politics principally in those lands in which music fell under state control, whereas West modernism was “abstract” in the fullest sense and ideologically neutral. Consequently, issues of music and politics mainly inhabited ghetto chapters in histories of twentieth-century music, walled off from discussions of new compositional techniques. Scholars seldom sought connections between musical decisions and ideological positions among composers of postwar music. Scholars are devoting ever more attention to matters of patronage, performance, and reception of new music, and they are grappling with the ideological associations of serialism, neoclassicism, indeterminacy and experimentalism. This new literature not only examines institutions that influenced musical development (such as music festivals in the West or composers’ unions in the East), but also the proclivities of the individuals who directed them. Amy C. Beal’s New Music, New Allies offers a detailed account of the West German patronage of American experimental music.